Contemplative life as an ideal of blessing in Thomas Aquinas’ moral philosophy - Pichler, Nadir Antonio; Oliveira, Talia Castilhos de (Revista Eclesiástica Brasileira, 2020)
The purpose of the text is to describe and analyze the contemplative life as an ideal of beatitude in the moral philosophy of Thomas Aquinas. By assimilating, remodeling and criticizing the ancient and medieval philosophical-theological tradition, Thomas structures an original and complex synthesis, immersing itself in the essence of the divine nature through knowledge and in the human soul through the contemplative life, and from there to erect the pillars of an ontology theocentric, where God is the supreme good and promoter of human happiness, the first principle of all reality. From him comes the world, man and all creatures, and everything tends to return to its essence, in a special the man. For this reason, God is the alpha and omega, propitiator of the deepest beatitude. The text is organized into four items: the context of beatitude, the excellence of the intellectual soul by the activity of the contemplative life, the reasons for the contemplative life and the comparison between the active and the contemplative life. Síntese: O objetivo do texto é descrever e analisar a vida contemplativa como ideal de beatitude na filosofia moral de Tomás de Aquino. Assimilando, remodelando e criticando a tradição filosófico-teológica antiga a medieval, Tomás estrutura uma síntese original e complexa, mergulhando na essencia da natureza divina pelo conhecimento e na alma humana pela vida contemplativa, para, a partir daí, erigir os pilares de uma ontologia teocentrica, onde Deus é o bem supremo e promotor da felicidade humana, o primeiro princípio de toda a realidade. Dele procede o mundo, o homem e todas as criaturas, e tudo tende a retornar a sua essencia, de modo especial, o homem. Por isso, Deus é o alfa e o ômega, propiciador da mais profunda beatitude. O texto está organizado em quatro itens: Contexto da beatitude, a excelência da alma intelectiva pela atividade da vida contemplativa, as razoes da vida contemplativa e a comparaçao entre a vida ativa e a contemplativa. Palavras-chave: Beatitude; Vida contemplativa; Filosofia moral; Tomás de Aquino; Deus.